Sharing tacit business knowledge between founder and successor in family business: case studies in Vietnam - Thanh Trung Pham; Robin Bell; David Newton (Faculty of Business, President University, 2018)
The purposes of this study are to explore in detail the tacit business knowledge transfer process and the effective transfer method from founder to successor in Vietnamese family businesses. This study, using separate interviews of paired founders and successors in five Vietnamese family businesses, aims to contribute to the general understanding of such processes in South East Asian family businesses. This study confirms that the tacit business knowledge transfer process is an on-going process until the founder is unable to continue due to physical or mental health preventing further communication. In addition, it indicates that the mentor-mentee method is the most common method for tacit knowledge transfer process. Storytelling is also a common process; unlike traditional Western SMEs, use of formal documentation tends to be far less prevalent as a way of transferring knowledge. The findings of this study show that not all of tacit business knowledge from the founder is important to the successor. Therefore, a successor needs time spent alone to contemplate each tacit business lesson, before determining whether to absorb it.